PENGARUH GAYA HIDUP SEHAT, GAYA KEPEMIMPINAN, DAN TIME BUDGET PRESSURE TERHADAP KINERJA AUDITOR PEMERINTAH - Rahmadhanty, Dwi Riski; Farah, Wilda (FAKULTAS EKONOMI DAN BISNIS ISLAM, 2020)
Introduction/ Purpose: This study aims to examine the influence of healthy lifestyle, leadership style, and time budget pressure on the performance of government auditors. Research Methods: This study uses primary data by distributing questionnaires to government auditors at 8 government institutions in Bangka Belitung Province. Sampling was done using convenience sampling method. The number of employees who became the sample in this study was 134 employees. The analytical method used to test the hypothesis is the multiple regression analysis using IBM SPSS Statistics 25. Results: The results showed that healthy lifestyle, leadership style, and time budget pressure has a significant effect on the performance of government auditors.